227k views
1 vote
S-rs=a-ar5 how do i solve for s

User Vesuvious
by
4.9k points

1 Answer

1 vote

Answer:

The value of s in the given equation is
(a(1-r^5))/(1-r)

Therefore
s=(a(1-r^5))/(1-r)

Explanation:

Given equation is
s-rs=a-ar^5

To find the value of s :


s-rs=a-ar^5

Taking common term "s" outside in LHS and common term "a" outside in RHS


s(1-r)=a(1-r^5)

Dividing by (1-r) on both sides we get


(s(1-r))/(1-r)=(a(1-r^5))/(1-r)


s=(a(1-r^5))/(1-r)

Therefore the value of s in the given equation is
(a(1-r^5))/(1-r)

Therefore
s=(a(1-r^5))/(1-r)

User Avocado
by
5.3k points